Reconstructing ancient mitochondrial DNA links between Africa and Europe - Cerezo, María; Achilli, Alessandro; Olivieri, Anna; Perego, Ugo A.; Gómez-Carballa, Alberto; Brisighelli, Francesca; Lancioni, Hovirag; Woodward, Scott R.; López-Soto, Manuel; Carracedo, Ángel; Capelli, Cristian; Torroni, Antonio; et al. (Genome Research, 2012)
Mitochondrial DNA (mtDNA) lineages of macro-haplogroup L (excluding the derived L3 branches M and N) represent the majority of the typical sub-Saharan mtDNA variability. In Europe, these mtDNAs account for <1% of the total but, when analyzed at the level of control region, they show no signals of having evolved within the European continent, an observation that is compatible with a recent arrival from the African continent. To further evaluate this issue, we analyzed 69 mitochondrial genomes belonging to various L sublineages from a wide range of European populations. Phylogeographic analyses showed that ∼65% of the European L lineages most likely arrived in rather recent historical times, including the Romanization period, the Arab conquest of the Iberian Peninsula and Sicily, and during the period of the Atlantic slave trade. However, the remaining 35% of L mtDNAs form European-specific subclades, revealing that there was gene flow from sub-Saharan Africa toward Europe as early as 11,000 yr ago.
10.1101/gr.134452.111